A Legal Perspective on the Organization–Volunteer Relationship. (April 2019) - Mead, Joseph
How does law view and shape the relationship between nonprofit organization and volunteer? To address this question, I draw on information from statutes, court decisions, and agency guidance from both the federal and state law in the United States. In general, "volunteer" is not a legally defined category in the United States, leaving a volunteer's legal status to depend on whether the volunteering aligns with other, recognized types of relationships, such as employer–employee, principal–agent, or program–participant. By providing a synthesis of these varied legal rules as they apply to volunteers working for a nonprofit organization, this piece identifies different ways of describing the relationship between organization and volunteer, and the legal obligations and benefits that flow as a result.